On The Legal Sanction Against Marriage Registration Violation in Southeast Asia Countries: A Jasser Auda’s Maqasid Al-Shariah Perspective - Harisudin, M Noor; Choriri, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
The legal sanction on marriage registration violations was intended to create equity within households and fulfill every citizen’s constitutional rights. However, the law enforcement efforts encountered some problems, especially in three Southeast Asia countries: Indonesia, Malaysia, and Brunei Darussalam. This article investigated the diversity of regulations on marriage registration violations in the countries and analyzed how Jasser Auda’s maqasid al-shariahperspective viewed the type of legal sanctions there. This study found that there were regulations on marriage registration violations in each country. However, while Malaysia and Brunei Darussalam imposed both financial penalty and imprisonment, Indonesia only charged fines for the culprits. In Jasser Auda’s perspective, the regulations in the countries, except Indonesia, were in line with maqasid al-shariah because firstly, they aimed at maintaining harmony in marriage and contained the aspect of serving the depth and breadth of public interest (maslahah) in terms of necessities (daruriyat). Secondly, the regulations had traversed basic conceptual approach and systems analysis.